Diagnostic reference level of radiation dose and image quality of adult CT abdominal examination based on body-mass index (BMI) in a tertiary hospital in Malaysia - Mohamad Ariffin, Mohamad Asmawi; Abdul Karim, Muhammad Khalis; Abd Rahman, Mohd Amiruddin; Mohd Zaid, Mohd Hafiz; Harun, Hanif Haspi (Universiti Putra Malaysia, 2024)
Introduction: Computed tomography (CT) ionising radiation may raise the risk of deterministic consequences and cancer development to the patient. Objective of this study is to determine the updated local DRL of adult CT abdominal examinations using a noise index to indicate the image quality. Materials and methods: A retrospective analysis was conducted on 200 adult patients who underwent CT abdominal examinations between January 2021 and December 2022 and categorised into three body mass index (BMI) groups; group 1, underweight (<18.5), group 2, overweight (≥25.0) and group 3, obese (≥30.0) and statistically compared the radiation dose exposure. The noise magnitude was quantitatively calculated by measuring the standard deviation of the circular region of interest (ROI) at five different locations around the abdominal area. The volume-weighted CT dose index (CTDIvol), the doselength product (DLP), and the effective dose (E) were computed for each BMI group, and DRLs were established with a 50th percentile set. Results: The highest radiation dose for CTDIvol, DLP and E was in group 3 (obese) with mean 15.44 ± 5.43, 769.78 ± 253.25 and 15.37 ± 4.74 respectively. Both DRL and noise reference levels between BMI groups have differed significantly with p-value < 0.05 and <0.70. Conclusion: Patients with varying BMIs had significantly variable radiation doses and noise intensities, necessitating the adjustment of some parameters to satisfy the clinical requirement.